Record of mandarin duck Aix galericulata (Linnaeus, 1758) from Lake Cluster of Pokhara Valley, Nepal - Baral, Milan; Timilsina, Binita; Neupane, Anisha (Nepalese Journal of Zoology, 2022)
The mandarin duck Aix galericulata (Linnaeus, 1758) is a vagrant species having very scarce sightings in Nepal. The record of the species from the Lake Cluster of Pokhara Valley has not been documented properly yet. This study presents the first record of the species from the Gunde Lake of Lake Cluster of Pokhara Valley as well as second record of the species from the Pokhara Valley itself. The species was recorded in the winter season on 18th December, 2021 while resting in the shore of Gunde Lake in the flock of lesser whistling duck Dendrocygna javanica.